Advanced biofuels : applications, technologies and environmental sustainability - Azad, Abul Kalam (Energy resources scholar); Rasul, Mohammad (UK: Woodhead Publishing, Elsevier, 2019)
Advanced Biofuels: Applications, Technologies, and Environmental Sustainability presents recent developments and applications of biofuels in the field of internal combustion engines, with a primary focus on the recent approaches of biodiesel applications, low emission alternative fuels, and environmental sustainability. Editors Dr. Azad and Dr. Rasul, along with their team of expert contributors, combine a collection of extensive experimental investigations on engine performance and emissions and combustion phenomena using different types of oxygenated fuel with in-depth research on fuel applications, an analysis of available technologies and resources, energy efficiency improvement methods, and applications of oxygenated fuel for the sustainable environment. Academics, researchers, engineers and technologists will develop a greater understanding of the relevant concepts and solutions to the global issues related to achieving alternative energy application for future energy security, as well as environmental sustainability in medium and large-scale industries.
2.4.4.1 The effect of utilizing biodiesel on hydrocarbon emission2.4.4.2 The effect of utilizing bioalcohol on hydrocarbon emission; 2.5 PARTICULATE MATTER EMISSIONS FROM IC ENGINES BURNING DIFFERENT BIOFUELS; 2.5.1 Particulate matter emissions from IC engines burning biodiesel; 2.5.1.1 Particle mass; 2.5.1.2 Particle size distribution; 2.5.1.3 Morphology and microstructure; 2.5.2 PM emissions from IC engines burning bioalcohol; 2.5.2.1 Particle mass and size distribution; 2.5.2.2 Morphology and microstructure; 2.6 GASEOUS EMISSIONS FROM JET ENGINES BURNING ALTERNATIVE JET FUELS.
Includes bibliographical references and index.
Keywords: Advanced biofuels; Bioénergie.; TECHNOLOGY & ENGINEERING -- Chemical & Biochemical; Biomass energy; Electronic books